Seasonal Fishery Closure in the Northern Bay of Bengal Causes Immediate but Contrasting Ecological and Socioeconomic Impacts - Islam, Mohammad Mahmudul; Begum, Amany; Rahman, Syed Mohammad Aminur; Ullah, Hadayet (Frontiers in Marine Science, 2021)
Bangladesh has introduced a monsoonal fishery closure in the Bay of Bengal. The reasoning is to ensure the conservation of fish stocks and productive breeding grounds. While the fishing ban has likely aided in boosting fish recruitment, it has also sparked protest and resentment among the small-scale fishers. This study investigates fishers’ perceptions towards the 65-day fishing ban between May and July in the Bay of Bengal. We collected both qualitative and quantitative data from five coastal fishing communities. Data were analyzed to explore fishers' perceptions of socioeconomic and ecological impacts of the closure. While most respondents agreed that the closure produced positive ecological outcomes, they felt that their income and food security had been negatively affected. Importantly, crew members perceived their losses to be more extreme as compared to the boat skipper or owner due to their overreliance on the fishery and lack of alternative skills and occupations. These fishers cannot forfeit their livelihoods and food security needs as they are already living on the margins of subsistence. This social ramification emphasizes the necessity of understanding the interconnection between fishers’ socioeconomic conditions and conservation needs. Thus, social-ecological tradeoffs and inequalities raise the question of social equity and environmental justice that could inevitably compromise management and conservation effectiveness and legitimacy. The involvement of local communities in the decision-making process for future fisheries interventions could enhance both livelihood opportunities and positive ecological outcomes in the Bay of Bengal marine ecosystem.